Viewpoint invariant reconstruction of 3D human skeleton from monocular images - Htike@Muhammad Yusof, Zaw Zaw (2010)
We present a fast, robust, fault-tolerant and nonparametric approach to reconstruct 3D human skeleton model from single images, regardless of the viewpoint of the camera relative to the observed person. The system achieves high degree of tolerance using search-based inference and probabilistic joint labeling. The system achieves 100% view invariance using a pruning-based parallel search algorithm.